HUBUNGAN KARAKTERISTIK IBU DAN PENYAPIHAN DINI DENGAN STATUS GIZI BALITA DI KELURAHAN OEPURA KOTA KUPANG - Christina R Nenotek; Marlastiany Takoy; Asweros Umbu Zogara (Journal of Innovation Research and Knowledge, 2024)
During infancy growth and development are the most important components of the growth and development process. This period determines the child's success in the future. The descriptive analytical research approach was used to investigate the relationship between maternal characteristics and early weaning with the nutritional status of toddlers in Oepura Village, Kupang City. The time frame for this study was January through may of 2024 in Oepura Village, Kupang City. In this study, toddlers made up the sample. When the study was conducted, 136 respondents were obtained. The instruments used were standard anthropometric tables, analytical scales and questionnaires. The Fisher-Exact statistical test was used to evaluate the relationships between the variables. The findings demonstrated that there was no connection between maternal knowledge (p-value = 0.120), maternal education (p-value = 0.324), maternal occupation (p-value = 0.071), and early weaning (p-value = 0.735) with the nutritional status of toddlers in Oepura Village, Kupang City. It is advised that health professionals regularly counsel moms of toddlers in order to increase their level of expertise